Investigating the impact of anatase on the dissolution of boehmite - Ireland, Myra; Wang, Xiaodong; Radomirovic, Tomoko; Smith, P.; Jones, Franca (Elsevier, 2014)
The dissolution of boehmite in synthetic Bayer liquors is inhibited in the presence of anatase. It has been suggested both by us and others (e.g. Loan et al., 2005) that dissolved titanate adsorbs onto the surface of the boehmite limiting its dissolution. This manuscript reports on digestion, X-ray diffraction (XRD) and transmission electron microscopy (TEM) investigations of boehmite solids partially dissolved in synthetic Bayer liquor in the presence of anatase. Energy filtered transmission electron microscopy (EFTEM) is used to obtain elemental distribution maps, which support the adsorption hypothesis and show enrichment of titanium on the boehmite crystals. Interestingly, the aluminium also becomes associated with some of the Ti-rich particles.